The Performance of V2O5:Ag Nanoparticles as Thin Film and Bulk Pellet Sensor for NO2 and NH3 Detection - Abdul-Ameer, Haidar J.; AL-Hilli, Muthafar F.; Ibrahim, Fuad T. (Iraqi Journal of Science, 2023)
A comparison of gas sensing performance of V2O5:Ag nanoparticles as thin film and as bulk pellet toward NO2 and NH3 is presented. V2O5:Ag nanoparticles thin films were deposited by vacuum thermal evaporation method on glass substrates while the pellets were prepared by powder technology. XRD patterns of thin film and pellet were polycrystalline with an orthorhombic structure. The value of average grain size is about 60 nm. The morphological properties of the samples have been distinguished by atomic force microscopy (AFM) and field effect scanning electron microscopy (FESEM) which indicated that the films showed homogeneous surfaces morphology and contained pores between the grains.  Sensing results showed a various response to NO2 and NH3 gases. It was found that the sensitivity of thin films sensor is superior to that of the pellets sensor.